(untitled) (Research, Society and Development, 2022)
The use of management practices that reduce the application of phytosanitary products and guarantee sustainability to the production process has been increasingly used in coffee farming. The objective of this work was to evaluate the vegetative, productive and nutritional parameters of coffee plants as a function of management systems. The experiment was set in 2018 in Monte Carmelo, Minas Gerais. The experimental design was in randomized blocks with four treatments and five blocks. The treatments were composed of doses of organic compost applied in topdressing: (T1): 150 g plant-1 (1.7 t ha-1); (T2): 300 g plant-1 (3.4 t ha-1); T3: 500 g plant-1 (5.7 t ha-1); and T4 (control: standard management of the farm). The conventional management provided an increase in the number of internodes in the plagiotropic branch of the coffee tree and in the productivity of the first crop of the plantation. The management systems did not influence the format and size of the coffee beans. The use of organic fertilization and absence of phytosanitary products allowed the production of specialty coffees, besides accelerating the maturation process of the fruits. The management with organic fertilization was efficient in keeping the pH, organic matter, base saturation, effective CEC, phosphorus, sulfur, calcium, copper, iron, manganese and zinc levels in the soil at satisfactory levels. The foliar levels of phosphorus, potassium, sulfur, boron and copper were satisfactory for the crop and did not differ between the management systems adopted in the field.